Building a Web 2.0 Portal with ASP.NET 3.5 - AL Zabir, Omar (Sebastopol, Calif. : O'Reilly Media, 2008)
Provides information on building an Ajax-based Web site using ASP.NET 3.5.
Introducing web portals and Dropthings.com -- Architecting the web portal and widgets -- Building the web layer using ASP.NET AJAX -- Building the data and business layers using .NET 3.5 -- Building client-side widgets -- Optimizing ASP.NET AJAX -- Creating asynchronous, transactional, cache-friendly web services -- Improving server-side performance and scalability -- Improving client-side performance -- Solving common deployment, hosting, and production challenges.
Includes index.
"Learn how to build a state-of-the-art Ajax web site using ASP.NET, .NET 3.5, LINQ, Windows WF, and more"--Cover.
"This guide provides a master class in site building with ASP.NET 3.5 and other cutting-edge Microsoft technologies. It teaches you how to develop rock-solid web portal applications that can withstand millions of hits every day while surviving scalability and security pressures--not just for mass-consumer home pages, but also for dashboards that deliverpowerful content aggregation for enterprises."--Back cover.
Keywords: Active server pages; Active server pages (Computer file); Active server pages (Computer software); Web site development; Microsoft .NET.; Web portals; Management -- Computer network resources; Internet programming; Web sites -- Design; Web sites -- Design; Microsoft .NET.